ANALISIS PERTUMBUHAN DAN HASIL TANAMAN SUNGKAI (Peronema canescens Jack.) DI KALIMANTAN - Wahyudi Wahyudi; Zainal Muttaqin; A. Russel Mojiol (JURNAL SAINS NATURAL, 2012)
Growth and Yield Analysis of Peronema canescens Jack. in Kalimantan          Sungkai (Peronema canescens) is a native and local species and one of some commercial trees which has a good prospect to be developed in timber estate in Kalimantan.This research was aimed to analyse sungkai plantation, neither the living percentage, productivity, economic cutting cycle, and also its profit. The data analysis was using the average of trees diameter, high and volume, mean annual increment, polynomial equation modelling and financial analysis i.e. net present value (NPV), benefit cost ratio (BCR) and internal rate of return (IRR). The research had been conducted at the community plantation in Kapuas District, Central Kalimantan Province since 1998 to 2010.  The result of this research showed that living trees precentage at 12 years old was 89.7%, mean annual increment and its density were 10,14 m3 ha-1  and 997 tree/ha respectively. Equation modelling of sungkai plantation was y = 2,073 + 1,6623x - 0,0165x2 (R2= 84,05%). In the bank rate of 9% per year, the economic cutting cycle of this plantation was 15 years with net present value was NPV 58,49 million per ha. BCR 7,64 and IRR 11,75 If the bank rate of 6% and 12% per year, then net present value at the 15 years were NPV 92.65 and 36.6 million per ha respectively. The sangtein was suitable as timber estate and to increase the productivity of former shifting cultivation, scru, and low potential forests which were widespread, especially in Kalimantan.Keywords :  Growth and yield, mean annual increment, Peronema canescens, economic cutting cycle ABSTRAK        Sungkai adalah jenis tanaman komersial lokal dan asli yang mempunyai prospek baik untuk dikembangkan dalam hutan tanaman Kalimantan. Penelitian ini bertujuan untuk mengetahui prosen hidup, produktivitas, siklus tebang optimum, dan keuntungan finansial dari tanaman sungkai. Penelitian dilakukan di hutan tanaman rakyat, Kabupaten Kapuas Provinsi Kalimantan Tengah. Obyek penelitian ialah tanaman sungkai yang ditanam sejak tahun 1998 pada tipe tanah Ultisol. Analisis data menggunakan nilai rataan diameter, tinggi dan volume, riap tahunan rata-rata tahunan, persamaan regresi, NPV, BCR dan IRR. Hasil penelitian menunjukkan bahwa pada umur 12 tahun prosen hidup tanaman mencapai 89,7 %, riap tahunan rata-rata 10,14 m3 ha-1 year-1 dengan kerapatan 997 pohon/ha. Model pertumbuhan tanaman sungkai ialah y = 2,073 + 1,6623x - 0,0165x2 (R2= 84,05%). Pada tingkat suku bunga pinjaman 9% per tahun, tanaman sungkai mempunyai siklus tebang ekonomi selama 15 tahun dengan nilai NPV Rp. 58,49 juta/ha, BCR: 7,64 dan IRR: 11,75%. Pada tingkat suku bunga pinjaman 6% dan 12% per tahun, maka pada siklus tebang selama 15 tahun, nilai NPVnya masing – masing menjadi Rp. 92,65 juta/ha dan Rp. 36,6 juta/ha. Tanaman sungkai sangat sesuai dikembangkan dalam hutan tanaman dan untuk meningkatkan produktivitas lahan bekas perladangan berpindah, semak belukar dan hutan potensi rendah yang tersebar luas, khususnya di Kalimantan.Kata kunci : Pertumbuhan dan hasil, riap tahunan rata – rata, Peronema canescens, siklus tebang ekonomi